Angioedema associated with nonsteroidal anti-inflammatory drugs. Issue 4 (August 2016) - Giavina-Bianchi, Pedro; Aun, Marcelo Vivolo; Jares, Edgardo José; Kalil, Jorge
Abstract : Purpose of review: The review critically assesses the different phenotypes of angioedemas associated with NSAIDs. Angioedemas exacerbated or induced by NSAIDs have high morbidity and, when they affect the larynx, can lead to death by asphyxiation. Recent findings: Angioedema can present as a manifestation of a syndrome such as anaphylaxis or it can be a separate entity, which comprises different forms that can be diagnosed based on specific criteria. NSAIDs are the drugs most used worldwide and they are also one of the leading causes of angioedema. Summary: The manuscript addresses the pathophysiology and pharmacogenetics of angioedema, reviews its classification and assesses the diagnosis and management of angioedemas exacerbated and induced by NSAIDs.